Targeting thioredoxin reductase in pancreatic cancer - Alhadyan, Khaled (2019)
Pancreatic cancer (PC) is the fifth leading cause of cancer deaths in the United Kingdom, and responsible for 5% of all cancer deaths. Current treatment options, including surgery, chemotherapy and radiotherapy, have failed to improve five-year survival rates over the last 30 to 40 years, which remain very low, at ~5%. A number of resistance mechanisms may explain this lack of treatment success, one of these being inherent or acquired expression of redox proteins, i.e. proteins that can scavenge therapy-induced radicals, making treatment, such as radiation therapy, less efficient. Redox proteins are key members of cellular antioxidant systems, required to maintain redox homeostasis, with the thioredoxin (Trx) system being an important component. The Trx system consists of Trx, thioredoxin reductase (TrxR), and thioredoxin-interacting protein (TxNIP). Trx exists in mammalian cells in either a reduced (functional) form or an oxidised (non-functional) form. The reduced form of Trx regulates the redox state of different signalling molecules, and by regulating their redox state, can regulate cell growth, apoptosis, gene transcription, cell cycle progression and ROS levels. TrxR is the only known enzyme that can reduce (activate) Trx. Therefore, TrxR has been studied as a potential therapeutic target in different types of cancer. Indolequinone analogues (IQs) are novel bioreductive TrxR inhibitors produced at the University of Nottingham, and currently being developed as potential drugs against PC. The current thesis set out to examine the role of the Trx system, using novel TrxR inhibitors, in regulating PC cell proliferation and radiosensitivity.